Experimental investigation of discrete sound production in deep cavity exposed to airflow - MEISSNER, M. (Archives of Acoustics, 1993)
The results are presented of the experimental investigation of the discrete sound generation in the process of airflow over the deep cavity. During the increase of the airflow velocity, three discrete components, referred to as A, B and C, are excited successively, which, as indicated by a analysis of results, are the f_13, f_12 and f_11 modes, respectively. In the process of sound generation two stages have been distinguished: stage 1, characterized by strong dependence of the frequencies of the discrete components A, B and C on the velocity of the airflow and stage 2, where the frequency, of the discrete component C, as the function of the velocity, varies approximately ten times less as compared with the stage 1. In stage 1 the "leading edge - trailing edge interaction" is of fundamental significance in the production of the discrete components, whereas the stage 2 is dominated by the feedback involving the effect of cavity-resonance modes on the disturbances of the shear layer.